Personal Testimony About Dealing with Loss and Self-Care - Selig, William P. (Journal of pastoral care & counseling, 2024)
As an interfaith hospital chaplain and a Christian, navigating the profound emotional terrain of grief and loss is both a professional duty and a deeply personal journey. Attending the funerals of two close friends has brought out the interplay between my role as a spiritual caregiver and my own vulnerability. In reflection, I realize the importance of self-care and the reminder that in offering comfort and empathy, I must first find it within myself.